Vahdat va hambastigi-yi shikastnapaziri niruhai-yi milli va vatanparasti Afghanistan (Hizbi Dimukrati Khalqi Afghanistan)
The indestructible unity and uniformity of the nationalist-patriotic groups of Afghanistan.